Daclizumab Versus Rabbit Antithymocyte Globulin in High‐Risk Renal Transplants: Five‐Year Follow‐up of a Randomized Study. Issue 7 (23rd February 2015) - Hellemans, R.; Hazzan, M.; Durand, D.; Mourad, G.; Lang, P.; Kessler, M.; Charpentier, B.; Touchard, G.; Berthoux, F.; Merville, P.; Ouali, N.; Squifflet, J.‐P.; et al.
<x xml:space="preserve">Abstract</x> We previously reported a randomized controlled trial in which 227 de novo deceased‐donor kidney transplant recipients were randomized to rabbit antithymocyte (rATG, Thymoglobulin) or daclizumab if they were considered to be at high immunological risk, defined as high panel reactive antibodies (PRA), loss of a first kidney graft through rejection within 2 years of transplantation, or third or fourth transplantation. Patients treated with rATG had lower incidences of biopsy‐proven acute rejection (BPAR) and steroid‐resistant rejection at 1 year. Patients were followed to 5 years posttransplant in an observational study; findings are described here. Treatment with rATG was associated with a lower rate of BPAR at 5 years (14.2% vs. 26.0% with daclizumab; p = 0.035). Only one rATG‐treated patient (0.9%) and one daclizumab‐treated patient (1.0%) developed BPAR after 1 year. Five‐year graft and patient survival rates, and renal function, were similar between the two groups. Overall graft survival at 5 years was significantly higher in patients without BPAR (81.0% vs. 54.8%; p < 0.001). In conclusion, rATG is superior to daclizumab for the prevention of BPAR among high‐immunological‐risk renal transplant recipients. Overall graft survival at 5 years was approximately 70% with either induction therapy, which compares favorably to low‐risk cohorts.